(untitled) (GYMNASIUM, 2011)
The functional physiotherapeutic treatment in cerebral palsy (CP) aims at the achievement of an as normal as possible functional capacity, and also at the development of some compensating mechanisms which ensure the possibility of self-management, education and work, respectively an active life, and, as much as possible, the perspective of economic and social independence. Using balance and rocking techniques within the functional physiotherapeutic programme will facilitate the achievement of relaxation, thus averting the actions performed by the child while attempting to oppose the stressing stimulus, which, in our case, is the new situation in which the child finds himself/herself, taking into account the close connection between the emotional state and the muscular tonus. That connection between the two tension situations creates a vicious circle which diminishes the child’s participation, thus impairing the development of the kinetic programme.